2013
DOI: 10.4028/www.scientific.net/amr.664.305
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Characteristics of Ammonium Nitrogen by Biochar from Diverse Origins in Water

Abstract: Corn straw biochar and peanut shell biochar were used as an adsorbent, duly affected by the condition of diverse concentrations of ammonium nitrogen, response times, the pH and temperature levels. The study focused on the adsorption characteristics of ammonium nitrogen by corn straw biochar and peanut shell biochar, which demonstrated that the adsorption rate of ammonium nitrogen by corn straw biochar and peanut shell biochar is higher in the initial response. The adsorption quantity rises quickly and attains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…EFBBC favorably eliminated NH 4 1 within a pH range of 6.0-10.0. Similar results were also observed for NH 4 1 removal by biochar [10]. At alkaline pH, the decrease in NH 4 1 elimination beyond pH10 is explained by the fact that NH 4 1 is partially transformed into electrically neutral NH 4 OH (NH 3 ÁH 2 O), which would decrease the isolation of NH 4 1 , and the volatilization of NH 3 leads to the loss of ammonia nitrogen.…”
Section: Effect Of Ph Adsorbent Dosage and Particle Size Onsupporting
confidence: 77%
“…EFBBC favorably eliminated NH 4 1 within a pH range of 6.0-10.0. Similar results were also observed for NH 4 1 removal by biochar [10]. At alkaline pH, the decrease in NH 4 1 elimination beyond pH10 is explained by the fact that NH 4 1 is partially transformed into electrically neutral NH 4 OH (NH 3 ÁH 2 O), which would decrease the isolation of NH 4 1 , and the volatilization of NH 3 leads to the loss of ammonia nitrogen.…”
Section: Effect Of Ph Adsorbent Dosage and Particle Size Onsupporting
confidence: 77%
“…On the other hand, although the r values from the Freundlich model were over 0.98 suggesting some level of physical adsorption, the values of 1/n <1, implied chemisorption was more favorable (Kizito et al 2015). Similar BC adsorption studies have reported that NH4 + adsorption fit both the Langmuir and Freundlich models (Liu et al 2013). From our results, the positive standard enthalpy change (ΔH°>0) indicated that pymetrozine adsorption process was endothermic.…”
Section: Discussionsupporting
confidence: 69%
“…Ma and other scholars have found that the Freundlich equation (R 2 =0.9762) is suitable for describing the behavior of the ammonia nitrogen adsorption of biochar, and the main form is the heterogeneous adsorption of the multi molecular layer [16,24,31,32,33] .…”
Section: Freundlich Adsorptionmentioning
confidence: 99%
“…The source of biochar with the adsorption effect to ammonia nitrogen is rich [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] . Furthermore, the different adsorption properties are demonstrated, as the biochars are made of different biomass materials [14,15] .…”
Section: The Research Progress In Adsorption Of Nitrate Nitrogen Usinmentioning
confidence: 99%